Pendampingan Rutin Maulid Dibak Sebagai Upaya Pelestarian Tradisi Keagamaan Di Desa Tambak Lekok Sanggaran - Muhammad Bashori; Nelud Darajatul Aliyah (Jurnal Pengabdian Masyarakat (Bisma), 2024)
Dibak's birthday activities are a religious tradition that has long been carried out in Tambak Lekok Village, Sanggaran. This tradition is a symbol of religious and cultural identity that is passed down from generation to generation. However, modernization, globalization and changes in people's lifestyles have become challenges in preserving this tradition. The Student Creativity Program (PKM) aims to provide routine assistance in the implementation of Maulid Dibak as an effort to preserve religious traditions. The methods used include regular outreach, training and mentoring involving religious leaders, youth and the wider community. The results of this activity show increased community participation, especially the younger generation, in religious activities as well as a deeper understanding of the cultural and spiritual values ??contained in Maulid Dibak. With routine assistance, it is hoped that this religious tradition can continue to be preserved amidst the increasingly rapid flow of modernization.